In situ layer formation on MgO–C refractories with different MgO grade by static and dynamic contact with liquid steel - Florian Kerber; Tilo Zienert; Konrad Kerber; Steffen Dudczig; Thomas Schemmel; Helge Jansen; Christos G. Aneziris (Open Ceramics, 2023)
Modern, high-quality steelmaking requires a comprehensive understanding of the behavior of refractories in service. Therefore, MgO–C refractories with different MgO grade were immersed once and twice into a steel melt at 1600 °C and 1680 °C, respectively, in a near-industrial steel casting simulator. The same materials were tested in static crucible melting tests. A coherent MgO layer containing low-melting phases and MgAl2O4 crystal-like structures formed on the specimens’ surface. The morphology and frequency of these structures were strongly related to the MgO grade of the specimens and the immersion procedure. A lower MgO grade caused an increased formation of low-melting phases, which contributed to a denser layer formed on the specimens’ surface, hampering gas diffusion and the formation of MgAl2O4 crystal-like structures. An increased steel melt temperature and the double immersion had a similar effect. Conversely, an excessive formation of MgO and/or MgAl2O4 was observed when the formed layer contained less low-melting phases.